The Relationship Between Family Support and the Stage of Hypertension in the Elderly - Rumba, Selfiani; Abudin, La Syam; Umamity, Syahfitrah (Omni Nursing Journal, 2024)
Background: The elderly experience role changes related to physiological and psychosocial changes. The increase in the elderly population will certainly be followed by an increased risk of suffering from chronic diseases, including hypertension. People with a chronic disease, such as hypertension, need support from the surrounding, especially family. Family is people who are always with and follow the life process of an individual. Objective: This study aimed to examine the relationship between family support and the stage of hypertension in the elderly. Methods: This study employed an analytical research design with a cross-sectional design. The population in this study was 60 people, with a total sample of 60 samples. The sampling technique used total sampling. Results: The majority of respondents had less family support, which accounted for 46 (76.7%) respondents. Most respondents suffered from stage 2 hypertension, which accounted for 34 (56.6%) respondents. The majority of elderly respondents who had good family support suffered from stage 1 hypertension, which accounted for 7 (11.6%) respondents. The Chi-Square test showed a p-value of 0.041. This indicated that there was a significant relationship between family support and the stage of hypertension in the elderly. Conclusion: There is a statistically significant association between family support and the stage of hypertension.